2021
DOI: 10.1371/journal.pone.0244328
|View full text |Cite
|
Sign up to set email alerts
|

On a new generalized lindley distribution: Properties, estimation and applications

Abstract: In this study, an extension of the generalized Lindley distribution using the Marshall-Olkin method and its own sub-models is presented. This new model for modelling survival and lifetime data is flexible. Several statistical properties and characterizations of the subject distribution along with its reliability analysis are presented. Statistical inference for the new family such as the Maximum likelihood estimators and the asymptotic variance covariance matrix of the unknown parameters are discussed. A simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…[8] studied the mathematical properties of the Lindley distribution in detail and applied it to a waiting time dataset, reigniting the interest of researchers. This sparked the introduction of several modifications of the Lindley distribution, including the extended Lindley distribution introduced by [9], the Lindley-Exponential distribution studied by [10], a generalized two-parameter Lindley distribution treated by [11], a three-parameter generalized Lindley distribution proposed by [12], the Marshall-Olkin generalized Lindley distribution studied by [13], and the new alpha power transformed power Lindley distribution developed by [14]. One relevant modification of the Lindley distribution is the power Lindley distribution developed by [15].…”
Section: Lifetime Distributions Have Become Increasingly Popular In S...mentioning
confidence: 99%
“…[8] studied the mathematical properties of the Lindley distribution in detail and applied it to a waiting time dataset, reigniting the interest of researchers. This sparked the introduction of several modifications of the Lindley distribution, including the extended Lindley distribution introduced by [9], the Lindley-Exponential distribution studied by [10], a generalized two-parameter Lindley distribution treated by [11], a three-parameter generalized Lindley distribution proposed by [12], the Marshall-Olkin generalized Lindley distribution studied by [13], and the new alpha power transformed power Lindley distribution developed by [14]. One relevant modification of the Lindley distribution is the power Lindley distribution developed by [15].…”
Section: Lifetime Distributions Have Become Increasingly Popular In S...mentioning
confidence: 99%
“…Let G(x, θ) be the cdf of the Lindley distribution given by (2). The cdf of Kw-Lindley distribution can be defined by substituting (2) into equation (3).…”
Section: Kumaraswamy Lindley Distribution (Kld)mentioning
confidence: 99%
“…Hafez, et al [13] presented a study on Lindley Distribution accelerated life tests, application and numerical simulation. AlgarniI [2] devoted a new generalized Lindley distribution properties, estimation and applications.…”
Section: Introductionmentioning
confidence: 99%
“…The one-parameter unit-Lindley distribution and its associated regression model for proportion data has been proposed by Mazucheli et al 28 Moreover, Algarni 29 suggested an extension of the generalized Lindley distribution using the Marshall-Olkin method. An extension of Lindley distribution has also been proposed by Maurya et al 30…”
Section: Transformed Lindley Distributionsmentioning
confidence: 99%